Membangun Keluarga Utama (MKU) dalam Pemberdayaan Masyarakat Marginal Studi BMT As Syafiiyah, Kotagajah Lampung Tengah - Aye Sudarto (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2019)
The program description empowers the economy of marginal communities. This requires moral support, meteriel from all parties by providing input to be able to support and improve for the benefit, benefit and welfare of the community. To be able to create prosperity, a society that can support community empowerment requires protection and professional management of the organization. The nature of the economic empowerment program is learning for the community, so that it can be agreed that the main element of empowerment is the development of the economic capacity of the community itself. The series of capacity building in economic empowerment conducted by BMT as Safiiyah consisting of socialization activities, implementation of empowerment, and provision of business capital have been carried out well, by using socio-economics related to social relations and daily life of the community.